Analysis Rules Haqiqah and Majaz in Interpreting the term Qawwamuna (QS. An-Nisa Verse 34) - Nurul Hamidah; Aswadi Aswadi; Meirando Rukhuz; Ahmad Syaifullah (Studia Quranika, 2025)
This study discusses the interpretation of QS. An- Nisā ' verse 34 has often sparked debate, particularly within feminist discourse and discussions of gender bias rooted in pre-Islamic patriarchal structures. Most interpretations of this verse tend to adopt a literal approach (ḥaqīqah), positioning men as leaders over women, based on the assumption that the verse is qa ṭ ' ī al- dalālah—textually definitive and not open to alternative interpretations. This study aims to critically assess that dominant approach by exploring the potential of using majāz (figurative meaning) to offer a more contextual and equitable understanding. The research employs a library-based method with a descriptive-analytical approach, examining relevant primary and secondary sources. The findings reveal that relying solely on a literal reading of the verse without considering its socio-historical context may lead to interpretive bias. Therefore, an integrative approach—balancing both the outward (literal) and inward (figurative) meanings—is essential to ensure that the Qur'anic message remains dynamic and relevant across time.